The impact of different regulatory models on the labour conditions, safety and welfare of indoor-based sex workers. (November 2014) - Pitcher, Jane; Wijers, Marjan
Drawing on research in the UK and the Netherlands, this article considers the respective legislative backgrounds, recent policy changes and their implication for sex workers in off-street environments. It considers the impact of different regulatory models on the employment rights, safety and welfare of sex workers and explores how working conditions in different indoor settings might be improved through legal and policy changes. We argue that although decriminalization of sex work is a precondition to secure the labour and human rights of sex workers, the involvement of sex workers in policy development and facilitation of different modes of working are necessary to improve their working conditions and autonomy.